The complete mitochondrial genome of the Emei black chicken (Gallus gallus) and its phylogenetic analyses - Jingjing Gu; Sheng Li (Mitochondrial DNA. Part B. Resources, 2020)
In this study, the complete mitochondrial genome of Emei black chicken (Gallus gallus) was obtained by using next generation sequencing method. The complete mitogenome sequence is 16,784 bp in length, containing 13 protein-coding genes, two ribosomal RNAs, 22 transfer RNA genes, and one control region. This work provides a valuable genetic resource of data for the Gallus gallus evolution study and contributes to the breeding improvement program of native chicken breeds.